2011
DOI: 10.1074/jbc.m111.285361
|View full text |Cite
|
Sign up to set email alerts
|

Two Distinct Sites in Sonic Hedgehog Combine for Heparan Sulfate Interactions and Cell Signaling Functions

Abstract: Background:The morphogen, sonic hedgehog, has important roles in development and disease and is in part dependent on heparan sulfate interactions. Results: Two sites in the protein are shown to contribute to heparan sulfate interactions and biological activity. Conclusion: A new site in sonic hedgehog is identified that regulates its biological activity. Significance: The data provide new insight into the important role of proteoglycan interactions with sonic hedgehog.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
72
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(80 citation statements)
references
References 41 publications
(51 reference statements)
8
72
0
Order By: Relevance
“…However, in Drosophila, when expressed in the Hh-receiving field, Sulf1 does not stimulate Hh signaling, but, on the contrary, reduces the response to the morphogen (Wojcinski et al, 2011). Accordingly, loss of Shh-HSPG interaction has been reported to reduce Shh signaling potency in vitro (Chang et al, 2011). These data, together with our present results showing that Sulf1 invariably activates Shh signaling in the neural tube, argue against Sulf1 acting in the immediate environment of Shh-receiving cells.…”
Section: Sulf1 Is Required Over Time For Neural Patterning Establishmsupporting
confidence: 72%
See 1 more Smart Citation
“…However, in Drosophila, when expressed in the Hh-receiving field, Sulf1 does not stimulate Hh signaling, but, on the contrary, reduces the response to the morphogen (Wojcinski et al, 2011). Accordingly, loss of Shh-HSPG interaction has been reported to reduce Shh signaling potency in vitro (Chang et al, 2011). These data, together with our present results showing that Sulf1 invariably activates Shh signaling in the neural tube, argue against Sulf1 acting in the immediate environment of Shh-receiving cells.…”
Section: Sulf1 Is Required Over Time For Neural Patterning Establishmsupporting
confidence: 72%
“…Furthermore, our data unambiguously show that MFP or LFP formation is not sufficient per se to activate expression of high Hh responsive genes at the correct time; instead Hh-expressing cells must express sulf1 to reach their full inductive potential. Shh is well known to interact with heparan sulfate (HS) chains and to preferentially bind HS chains having a high level of sulfation (Carrasco et al, 2005;Chang et al, 2011;Dierker et al, 2009;Farshi et al, 2011;Zhang et al, 2007). Therefore, as reported for other signaling molecules (Ai et al, 2003;Freeman et al, 2008;Viviano et al, 2004), Sulf1 activity is likely to lower Shh-HSPG interaction.…”
Section: Sulf1 Is Required Over Time For Neural Patterning Establishmmentioning
confidence: 99%
“…Heparan sulfate and heparin binding of various morphogens, cytokines, chemokines, growth factors, proteases and protease inhibitors is mediated by clusters of basic amino acids on their surfaces. In vertebrate Hh proteins, heparan sulfate is mainly bound by the Cardin-Weintraub motif BBBxxBB (B represents a basic amino acid, x represents any amino acid) (Cardin and Weintraub, 1989;Chang et al, 2011;Farshi et al, 2011;Rubin et al, 2002), but Cardin-Weintraub residues also constitute the Nterminal Hh sheddase cleavage site (Ohlig et al, 2012). This suggests a possible mode of processing regulation by competitive heparan sulfate binding, consistent with recently described HSPG bioactivities in Hh-producing cells (Ayers et al, 2010;Bilioni et al, 2013;Oustah et al, 2014;Wojcinski et al, 2011).…”
Section: Introductionsupporting
confidence: 48%
“…Thus, we confirmed that Nterminally processed clusters are significantly more active than comparable amounts of largely unprocessed proteins. Note that the N-terminal CW sheddase target site also represents the binding site for heparan sulfate proteoglycans on the surface of Shh-producing cells (Chang et al, 2011;Farshi et al, 2011;Vyas et al, 2008); this suggests a possible mode of regulation of Shh release.…”
Section: Sheddases Release Dual-lipidated Shhnp From Producing Cellsmentioning
confidence: 99%